Effect of Job Burnout on Employee Performance: Field Research in the General Company for Vegetable Oil Industry - علي العزاوي شفاء محمد; عبدالله ساره لعيبي (Journal of Economics and Administrative Sciences, 2020)
Abstract This research aims to know the effect of job burnout in the worker’s performance. The researcher presented a theoretical basis for job burnout and the worker’s performance. In order to achieve the objectives of the research, a hypothesis was drawn up that determines the nature of the relationship between the independent variable of job burnout and its dimensions (reduced personal accomplishment, depersonalization, Emotional Exhaustion) and variable dependent performance of workers dimensions (productivity, job satisfaction, organizational commitment, creativity), And to represent the volume of this community according to (de Morgan, D. Morgan) global; to represent difficulty at the level of significance (0.05), and up to (0.01), in order to identify the nature of the relationship between the variables adopted, the research sets main and sub-emanating hypotheses from them. In order to test the hypotheses of the research, the research was carried out by the employees of the General Company for Vegetable Oil Industry for the purpose of obtaining the necessary information through a questionnaire prepared for this purpose distributed to the same number (130) individuals representing the middle and lower administrative levels in different sections and used a total Statistical methods such as relative frequency, arithmetical mean, standard deviation, and coefficient of variation for the measurement and analysis of the same research hypotheses and the simple correlation coefficient Pearson to measure correlation between the variables and (t-test) for his knowledge of the relationship of simple correlation and multiple regression analysis. The research has reached a number of conclusions, the most important of which is that the presence of functional combustion in the company contributes to low levels of functional performance the existence of a strong correlation between the functional combustion and productivity, and it turned out that the variable sintering the emotions the strongest dimensions of the absence of any correlation between the effect and performance added to that provided The researcher ’s group of recommendations was the most important reduction of the phenomenon of combustion functional and work on the development of preventive treatments benefit the company investigated